Mechanics of Psoas Tendon Snapping. A Virtual Population Study - Audenaert, Emmanuel A.; Khanduja, Vikas; Claes, Peter; Malviya, Ajay; Steenackers, Gunther (Frontiers in Bioengineering and Biotechnology, 2020)
Internal snapping of the psoas tendon is a frequently reported condition, especially in young adolescents involved in sports. It is defined as an increased tendon excursion over bony or soft tissue prominence causing local irritation and inflammation of the tendon leading to groin pain and often is accompanied by an audible snap. Due to the lack of detailed dynamic visualization means, the exact mechanism of the condition remains poorly understood and different theories have been postulated related to the etiology and its location about the hip In the present study we simulated psoas tendon behavior in a virtual population of 40 000 anatomies and compared tendon movement during combined abduction and external rotation. At risk phenotyopes for tendon snapping were defined as the morphologies presenting with excess tendon movement. There were little differences in tendon movement between the male and female models. In both populations, abnormal tendon excursion correlated with changes in mainly the femoral anatomy (male r 0.72, p < 1e-300, female r 0.66, p < 1e-300): increased anteversion, valgus and medial bowing. The observed combination of shape components correlating with excess tendon movement further presented with a decreasing ischiofemoral distance by a profound medial positioning of the minor trochanter. This finding suggest that psoas snapping and ischiofemoral impingement are possibly two presentations of a similar underlying rotational dysplasia of the femur.